2014
DOI: 10.1177/230949901402200306
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Plate Osteosynthesis for Distal Tibial Fractures

Abstract: Purpose.To review the outcomes of 53 patients who underwent minimally invasive plate osteosynthesis (MIPO) for distal tibial fractures. Methods. Medical records of 31 men and 22 women aged 22 to 78 (mean, 51) years who underwent MIPO using a locking compression plate for distal tibial fractures of the left (n=28) and right (n=25) legs with or without intra-articular extension were reviewed. Results. Patients were followed up for a mean of 26 (range, 24-38) months. The mean time from injury to surgery was 9 (ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
1
10
0
2
Order By: Relevance
“…The MIPO technique has gained popularity recently because of its satisfactory clinical outcomes123456789101112. This method minimizes disruption of soft tissue and preserves the blood supply to the fracture site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MIPO technique has gained popularity recently because of its satisfactory clinical outcomes123456789101112. This method minimizes disruption of soft tissue and preserves the blood supply to the fracture site.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive plate osteosynthesis (MIPO) has gained popularity because it minimizes dissection of broken bone fragments and therefore preserves vascularity and increases the healing potential123456789101112. It provides adequate stability and is a safe, effective method for both comminuted and simple fractures6111314.…”
mentioning
confidence: 99%
“…With the development of minimally invasive technology, minimally invasive plate osteosynthesis (MIPO) has become an excellent method. It protected the subcutaneous soft tissue of anterior medial tibia and enabled adequate soft tissue coverage overlying the plate with less wound complications.…”
Section: Introductionmentioning
confidence: 99%
“…This was comparable to a study by Devkota et al, which also showed similar operative times. 15 The mean blood loss during the surgery for distal tibial fracture using minimally invasive plate osteosynthesis was 75 ml which is significantly less compared to the traditional open reduction internal fixation with plates. This is possibly due to the smaller incisions and non-usage of negative suction drains in cases of MIPO for distal tibial fractures.…”
Section: Resultsmentioning
confidence: 96%